The Implementation of Cooperative Learning: A Case Study at International Primary Classroom - Nafsiyah, Zakiyatun; Karmina, Sari; Sujiatmoko , Ahmad Heki (Institut Agama Islam Negeri Madura, 2025)
Abstract: Cooperative learning (CL) is an instructional approach that facilitates students’ knowledge construction through collaborative interaction in small groups. This qualitative case study explores how CL has been applied in an international primary classroom setting where located in Gresik East Java Indonesia. Two English teachers were interviewed using semi-structured interview and their classes were observed to collect the data. The data were analysed using thematic analysis. The findings showed that CL enhances active engagement, collaboration, and cognitive learning. However, teachers faced several barriers in implementing CL, including time constraints, differences in student’s skill levels, and classroom management. To address these challenges, teachers employed diagnostic assessments, flexible grouping, and structured reflections. These findings suggest that while CL is beneficial, its success depends on sufficient teacher training, especially in culturally diverse classrooms. The study underscores the importance of sustained professional training and adaptive strategies to maximize the effectiveness of CL in multicultural setting.